Sediment capping technology for eutrophication control and its potential for application in Indonesian lakes: a review - Astried Sunaryani; Prayatni Soewondo; Arianto Budi Santoso (LIMNOTEK Perairan Darat Tropis di Indonesia, 2023)
Eutrophication occurs when the lakes become enriched with nutrients. Some nitrogen and phosphorus fractions will settle in sediment, and others will be released back into the overlying water column. Excess nutrients in water bodies resulting in hypoxic to anoxic conditions that can cause a mass fish death. Hence, we need a sediment management strategy to minimize resuspension and transport of sediment back into the water column. Sediment capping is a containment technology to reduce the release of nutrients from sediment as a strategy for eutrophication control. This study aims to provide insight into sediment capping technology, including several considerations in capping design, as well as information on several active materials that have been applied as capping materials and their efficiencies. Capping materials such as calcite, zeolite, bentonite, activated carbon, sludge, biochar, and gypsum from previous studies showed the efficiency of 54–99 % nutrient reduction with capping duration of 10–300 days in some eutrophic lakes. Sediment capping technology has successfully promoted lake ecosystem restoration in other countries, and this technology has the potential to be applied in Indonesian eutrophic lakes as a strategy for eutrophication control and sustainable management of lake ecosystems by considering the selection of the most effective, efficient, easy, inexpensive, and eco-friendly capping materials.